Evaluation of The Chronic Disease Management Program (PROLANIS) on The Management of Diabetes Mellitus Patients - Fandy Akbar Brilliantama; Burhannudin Ichsan (LPPM STIKes Muhammadiyah Ciamis, 2026)
Background: The Chronic Disease Management Program (Program Pengelolaan Penyakit Kronis/PROLANIS) is a strategic initiative implemented in primary health care center to improve the management of chronic diseases, including diabetes mellitus. This program emphasizes comprehensive, continuous, and patient-centered care. However, variations in program implementation at the primary care level may influence its effectiveness, highlighting the need for in-depth evaluation. Methods: This qualitative case study was conducted at Nogosari Primary Health Care Center, Boyolali. Informants included 15 diabetes mellitus patients participating in PROLANIS and 2 health care providers. Data were collected through observation, in-depth interviews, and document review, then analyzed using content analysis. Results: Most PROLANIS components, such as medical consultations, health education, physical activity, health monitoring, and SMS reminders, were implemented according to guidelines and showed positive contributions. Supporting factors included comprehensive medical services, effective support systems, and peer support among participants. However, barriers remained, including limited access to services and medications, suboptimal service quality, low motivation, awareness, and adherence among some participants, and underutilized home visit activities. Overall, PROLANIS encouraged healthier lifestyles, improved medication adherence, and increased patient knowledge. Conclusions: PROLANIS demonstrates significant potential in supporting diabetes mellitus management in primary health care center. However, improvements are needed in terms of service accessibility, program personalization, and patient engagement to enhance program effectiveness and sustainability